The Impact of Implementing Kahoot! & Windows Shopping Learning Model on Learning Interest of Class X DKV1 SMK N 3 Surakarta Students in Basic DKV Subjects - Maryanti; Chaizara, Rezza Fariszal Hisyam; Liantoni, Febri (Journal of Global Hospitality and Tourism Technology, 2024)
This research was conducted to find out the effect of implementing Kahoot! and the Windows Shopping learning model on the learning interest of class X DKV1 SMK N 3 Surakarta students in the Basic DKV subject. This is important because students' interest in learning is one of the determining factors for learning that has been designed to run effectively. The method used in this research is qualitative in the form of questionnaires and interviews with 36 class X DKV1 students. The analysis technique in this research uses descriptive analysis and thematic analysis. After data analysis, it can be concluded that implementing Kahoot! and the Windows Shopping model has a positive influence on students' interest in learning as evidenced by the results of questionnaire analysis & interviews which state that every aspect of interest in learning (Happy, Interested, Attentive, Involved) is fulfilled and gets positive perceptions from all students.